Exploring the inclusion of dogs in online personal branding - Graaff, Pieter Christiaan (The IIE, 2024)
The rapid advancement in technology has evolved the relationship between people, branding and dogs in the twenty-first century. With the rise of popular social media platforms such as Instagram and Facebook, people have become publishers of their own lives, freely sharing their experiences with others on a global scale. This has made it easier than ever for people to construct and create their own online personal brands, some of which include dogs, as an integral component of their online identities. This phenomenon, in which people actively include their dogs as part of their online personal branding, has remained largely unexplored, warranting comprehensive investigation. The primary objectives of this qualitative study were to further investigate personal branding and to explore why and how online personal brands incorporate dogs as well as to determine the extent to which people are aware of the ethical implications of these practices for their pets. Guided by the literature review, this study incorporated research on brand identity, brand image, personal and online branding, self-presentation, the evolving function and values of dogs, and the ethical considerations surrounding the inclusion of dogs in online contexts. The study employed an exploratory methodology, utilising qualitative research methods to gain an in-depth understanding of the research question: why and how people incorporate dogs into their online personal branding and whether they are aware of the ethical implications of such practices for dogs. The population and unit of analysis comprised individuals who frequently featured their dogs on their personal social media accounts, with a specific focus on Instagram and Facebook users. A non-probability sampling approach was implemented, and the final sample was purposively selected by the researcher. Seven qualitative, in-depth, semi-structured interviews were conducted to gain deeper insights into the motivations and methods used by the participants when incorporating their dogs into their online personal brands and to assess their awareness of potential ethical implications it might have for dogs. When analysing the qualitative data, a thematic analysis approach was employed, unveiling themes, categories, and patterns that provided rich insights into understanding this phenomenon. iii The insights from this study underscore the extensive impact of social media on personal branding, as individuals leverage these platforms to shape their online identities, often incorporating their dogs as integral elements of their extended selves. By featuring their dogs, individuals render their online personal brands more relatable and approachable, facilitating more meaningful connections with their audience. People include their dogs for a variety of reasons and in novel ways, which appears to enhance the appeal of their online personal brands. Notably, the findings highlighted the varying degrees of awareness individuals possess regarding the ethical implications when showcasing their dogs in their daily posts. The insights generated by this study enrich and contribute to the discipline of personal branding, offering a deeper understanding of the motivations and strategies used by people when including their dogs in their online personal brands. It also addresses the gap in the existing literature concerning the understanding of this phenomenon and the possible ethical considerations that need to be contemplated by online personal brands when including their pets. Lastly, this research serves as a valuable framework for individuals seeking to enhance and add value to their online personal brands. From a brand leadership perspective, this study can prompt reflection for corporate brands that are unaware of the potential ethical implications associated with incorporating dogs into their branding efforts.
Keywords: Brand identity; Brand image; Personal branding; Brand extension; Ethics; Self-presentation